O Judiciário e a incorporação de tecnologias em saúde: uma análise de decisões sobre concessão de fármacos não incorporados ao SUS sob o paradigma da Crítica Hermenêutica do Direito - Faria, Lucas Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Health judicialization is a growing reality in Brazil that, ultimately, may represent the Judicial Power as an way to ensure the health fundamental right effectiveness, and might become an undue intervention capable of provoking unwanted budget deallocation and, even further, compromising the public politics execution of public health, causing judicial activism. Due to the persistent judicial interventions in public health matters, CONITEC (National Commission for the Incorporation of Technologies into the Unified Health System, also known as SUS) was established by Federal Law n. 12.401/2011, which lays out about therapeutics assistance and technology incorporation into the health public system. CONITEC is responsible for recommending to the Health Ministry the incorporation, exclusion, or alteration, within SUS, of the National List of Essential Medicines (RENAME), in other words, the medicines that must be provided to the population due to the system. As widely known, there are countless technological innovations in healthcare, mainly due to the post-modern concept of increasing life expectancy. This is why CONITEC is frequently tasked with evaluating the incorporation of new drugs into SUS. This study aims to analyze decisions made by the São Paulo State Court that compels the State to provide the population with medications not included in SUS due to administrative decisions based on CONITEC recommendations, drawn from the theoretical contribution of Hermeneutic Critique of Law, focused on cases adjudicated in Ribeirão Preto City, State of São Paulo, between 2020 and 2022, using a hermeneutic approach method from an inductive perspective, and data collection method through documental and bibliographical research, in addition to jurisprudential research with a qualitative perspective through content analysis. The study's intention is to clarify whether, in the analyzed cases, it is possible to conclude whether the expected phenomenon of health judicialization occurs or if there is the unwanted misunderstanding of judicial activism. The conclusion is that judicial decisions do not satisfy the argumentative burden imposed by the Hermeneutic Critique of Law on judicial intervention in social fundamental rights, disregarding completely the existence of the legally established health technology evaluation system, asserting a conception of the fundamental right to health that encompasses any drug prescribed by a M. D., thus becoming a severe example of judicial activism.

A judicialização da saúde é uma realidade crescente no Brasil que, em verdade, pode representar a atuação do Poder Judiciário com fins de assegurar a efetivação do direito fundamental à saúde, como também pode se transformar em intervenção indevida capaz de provocar desalocações orçamentárias indesejadas e, até mesmo, comprometer a execução de políticas públicas em prol da saúde coletiva, configurando ativismo judicial. Por força das constantes intervenções do Poder Judiciário em matéria de saúde pública, foi criada a CONITEC (Comissão Nacional de Incorporação de Tecnologias no SUS), a partir da Lei Federal 12.401/11, que versa sobre a assistência terapêutica e a incorporação de tecnologia em saúde no SUS. A CONITEC é responsável por recomendar ao Ministério da Saúde a incorporação, exclusão ou alteração, no âmbito do SUS, da Relação Nacional de Medicamento Essenciais (RENAME), ou seja, aqueles que devem ser oferecidos pelo sistema à população. Como é sabido, as inovações tecnológicas na área da saúde são inúmeras, principalmente pela ideia pós-moderna de prolongação da vida ser cada vez mais presente, razão pela qual a CONITEC acaba por ser frequentemente demandada quanto à análise da possibilidade de incorporação de novos fármacos ao SUS. O presente trabalho aspira realizar uma análise de decisões do Tribunal de Justiça do Estado de São Paulo que obrigam o Poder Público a conferir ao cidadão medicamentos não incorporados ao SUS por decisão administrativa fundamentada em recomendações da CONITEC, a partir dos aportes teóricos da Crítica Hermenêutica do Direito, utilizando-se de casos ajuizados na Comarca de Ribeirão Preto/SP entre 2020 e 2022, a partir de um método de abordagem hermenêutico em uma perspectiva indutiva, se valendo do método de procedimento de levantamento de dados, por meio da pesquisa bibliográfica e documental, além da pesquisa jurisprudencial com uma perspectiva qualitativa a partir da análise de conteúdo, com fins de esclarecer se – nos casos analisados – podemos concluir que ocorre o esperado fenômeno da judicialização da saúde ou o indesejável equívoco do ativismo judicial. Conclui-se que as decisões judiciais não satisfazem o ônus argumentativo imposto pela Crítica Hermenêutica do Direito para a intervenção do judiciário em matéria de direitos fundamentais sociais, de modo que ignoram totalmente a existência de um sistema de avaliação de tecnologias em saúde instituído por lei, afirmando uma concepção do direito fundamental à saúde que inclui todo e qualquer insumo que seja receitado pelo profissional médico, representando grave exemplo de ativismo judicial.
The Judiciary and the technology incorporation into the heal public system: an analysis of decisions about not recomendeed medications by Conitec drawn from the theoretical contribution of Hermeneutic Critique of Law
Keywords: Judicialização; Ativismo; Saúde; CONITEC; Crítica Hermenêutica do Direito; Judicialization; Activism; Health; Hermeneutic Critique of Law; CONITEC